Electrospun Fibers of Enteric Polymer for Controlled Drug Delivery - Fábia F. P. da Costa; Evando S. Araújo; Marcio L. F. Nascimento; Helinando P. de Oliveira (International Journal of Polymer Science)
The production of electrospun fibers of enteric polymer for controlled delivery of drugs represents a simple and low cost procedure with promising advantages relative to the longer therapeutic window provided by cylindrical geometry in association with intrinsic properties of pH-dependent drug carriers. In this work, we have explored the incorporation of additives (block copolymers of poly(ethylene)-b-poly(ethylene oxide)) into matrix of Eudragit L-100 and the effective action of hybrid composites on delivery of nifedipine, providing improvement in the overall process of controlled release of loaded drug.